PENGARUH LOCUS OF CONTROL INTERNAL DAN PENDAPATAN TERHADAP LITERASI KEUANGAN MAHASISWA - Susanti, Susanti (UNIVERSITAS NEGERI SURABAYA, 2016)
This study aimed to analyze the influence of internal Locus of Control and the income of students to the financial literacy of students of Faculty of Economics in Universitas Negeri Surabaya either partially or simultaneously. The population in this study is the Faculty of Economics Study Program S1 and S1 Accounting Accounting Education in Universitas Negeri Surabaya years 2012-2014. The sampling technique used in this research is proportional probability sampling area. While the method of analysis using multiple linear regression analysis. The results of data analysis showed that partially Internal Locus of Control has positive significant effect on the financial literacy of students. While income has significant negative effect on the financial literacy of students. The results of the analysis of simultaneous data Internal Locus of Control and earnings significantly influence the financial literacy of students of Faculty of Economics at the State University of Surabaya